Mali : Fourth Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines Mali's Fourth Review Under the Poverty Reduction and Growth Facility (PRGF) Arrangement and Request for Waiver of Performance Criteria. The implementation of the PRGF-supported program was satisfactory in 2001. All the end-December 2001 and end-March 2002 quantitative performance criteria and benchmarks were observed. However, two structural performance criteria for end-December 2001 that concerned the cotton sector were not observed. Real GDP is expected to grow by 9.3 percent in 2002, compared with the 6.7 percent anticipated under the original program.